Case Study of the Application of Ways to Increase Outreach to Patients with Social Isolation Problems at the Puskesmas Bandar Jaya Lahat - A. Gani; Echa Hastuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Social isolation is an attempt to avoid interactions and relationships with people. It is characterized by a flat, sad affect, wanting to be alone, an inability to meet other people's expectations, feeling insecure in public places, a history of being rejected, no eye contact, and not having a purpose. The purpose is to learn how to get to know clients in social isolation and to find out the effect of getting to know clients on clients Mrs. H. and Mrs. L. in the working area of the Bandar Jaya Lahat Health Center in 2022. The form of research used is descriptive direct interviews with clients experiencing social isolation, namely making acquaintances and chatting. Results: Reducing signs and symptoms of social isolation and being able to socialize with others.